Amounts of Nitrogen and Phosphorus Related to Agricultural Pollution Elements in Egirdir Lake - ATILGAN, ATILGAN; COSKAN, ALI; ISLER, ERDINC; OZ, HASAN (Asian Journal of Chemistry, 2010)
Egirdir lake having surface area 482 km2, is an inward lake of which is oligotrophic, used for drinking water, irrigation, fishery products, tourism, recreation, fishing and wild life. Lake is potentially polluted by the residential districts as well as agricultural areas. Egirdir lake with its potable water and blue-flagged beach is under the threat of pollution due to the arrival of agricultural and household wastes together with leather industrial wastes in uncontrolled manners. In recent years, the existence of the noticeable green cover in some bays within the lake has made. It is thought that agricultural pollutant elements have reached the lake therefore water samples were taken from the lake in order to identify the concentration of manures with nitrogen and phosphorus which are the most used mineral manures in agriculture. As the sampling points, Kovada lake exit with the inclusion of the close areas on both sides of this exit, the bays on which green cover has occurred, the coast close to the residential districts, the regions with a coast to the agricultural areas and the coastlines with natural vegetation were chose. In the water samples taken from 15 points for the analysis of NH4+, NH3, NO3–, NO2– and P2O5 were carried out. In the first period of sampling ammonium nitrogen was not found in 3 points. The highest NH4+ amount found in other points 0.02 mg NH4+-N/L. In none of the samples ammonia nitrogen was found. Although there are some differences in water samples with regard to NO3--N contents, the defined values in most of the samples were found to be lower in comparison with the acceptable limit values. In none of the samples, NO2– amount was found enough to be analyzed. When the values obtained through phosphorus content were examined, 0.096 mg P2O5 L-1 was found only on the point where residential districts and agricultural areas exist together. In other sampling points, phosphorus levels were found as zero value or that is close to zero. Based on these results, it has been concluded that agricultural production carried out in the region is likely to cause nitrogen and phosphorus pollution throughout the lake. In this study, it has been clearly seen that the actions in which plant nutrient components are defined need to be condensed during the days especially following the manure periods in the bays with lesser water movements within the lake.